Prinsip Individualisasi Pidana Dalam Penempatan Narapidana Berdasarkan Jenis Kejahatan - Anggian Cassilas; Rugun Romaida Hutabarat (UNES Law Review, 2023)
The development of prisoners in prison aims to foster prisoners so that they do not repeat their crimes and become better individuals so that they can be accepted back into society. In fostering prisoners, the classification of prisoners must be applied. The classification of prisoners is an application of the principle of individualization. The principle of individualization of punishment is one part of the purpose of punishment. Article 12 of Law Number 12 Year 1995 on Corrections once regulated the classification of prisoners based on the type of crime. In its amendment, namely in Article 36 paragraph (4) of Law Number 22 Year 2022 on Corrections, it no longer regulates the classification of prisoners based on the type of crime. The placement of prisoners is only classified based on age and gender or other reasons based on risk assessment.